2017
DOI: 10.1016/j.exer.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 regulates Müller glia reprogramming and proliferation in the regenerating zebrafish retina via Lin28 and Ascl1a

Abstract: Sox2 is a well-established neuronal stem cell-associated transcription factor that regulates neural development and adult neurogenesis in vertebrates, and is one of the critical genes used to reprogram differentiated cells into induced pluripotent stem cells. We examined if Sox2 was involved in the early reprogramming-like events that Müller glia undergo as they upregulate many pluripotency- and neural stem cell-associated genes required for proliferation in light-damaged adult zebrafish retinas. In the undama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 55 publications
(122 reference statements)
3
104
0
1
Order By: Relevance
“…As a result, the Müller glia-derived regeneration of cone photoreceptors fails, but rod photoreceptors are eventually replenished. This observation is consistent with previous reports that also identified separate lineages between regenerated cone and rod photoreceptors (Gorsuch et al, 2017;Morris et al, 2008;Thummel et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As a result, the Müller glia-derived regeneration of cone photoreceptors fails, but rod photoreceptors are eventually replenished. This observation is consistent with previous reports that also identified separate lineages between regenerated cone and rod photoreceptors (Gorsuch et al, 2017;Morris et al, 2008;Thummel et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…In response to neuronal cell death, Müller glia spontaneously reprogram, upregulating stem cellassociated genes prior to entering the cell cycle (Goldman, 2014;Gorsuch and Hyde, 2014;Hamon et al, 2016;Lenkowski and Raymond, 2014). Immunostaining retinas at 1 and 2 dpl for the stem-cell associated proteins, Rx1 and Sox2, labeled elongated, polygonal nuclei, characteristic of Müller glia (Nagashima et al, 2013) (Gorsuch et al, 2017), in both wildtype and mutant retinas (Fig. 4A).…”
Section: Müller Glia In the Mdka Mi5001 Mutants Undergo Gliotic Remodmentioning
confidence: 98%
“…Reactive gliosis is a critical step in the formation of MGPCs, as loss of function of genes that are highly enriched in reactive MG such as hmga1a in zebrafish and FABP family genes in chick blocks the formation of MGPCs. Previous studies in zebrafish have likewise identified multiple genes that show enriched expression in reactive MG --such as six3b, sox2, lepb and others (25,35,45) --to also be essential for MGPC formation.…”
Section: Discussionmentioning
confidence: 88%
“…TET1-2 are important for ESC linage specification [93,94]. TET1 plays an important role during DNA demethylation and gene expression in mouse ES cells [86][87][88]95] while TET3 contributes to genome-wide DNA demethylation and can efficiently reprogram fibroblast directly into functional neurons and induce demethylation of Ascl1, an important factor for MG reprogramming in mouse and zebrafish [96][97][98][99][100][101][102]. Moreover, TET3 is required for significant axon regeneration in the dorsal root ganglion (DRG) neurons, suggesting that an epigenetic barrier can be removed by active DNA demethylation mediated by TET3 [103].…”
Section: Discussionmentioning
confidence: 99%